2003
DOI: 10.2166/wst.2003.0301
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide, dinitrogen and methane emission in a subsurface flow constructed wetland

Abstract: N2O, N2 and CH4 fluxes were measured from a horizontal subsurface flow (HSSF) constructed wetland (CW) for wastewater treatment in Estonia. The closed chamber method was used in the field and the He-O method (intact soil core analyses) in the lab throughout the period from October 2001 to June 2002. The average flux of N2O-N, N2-N and CH4-C from various microsites ranged from 0.1 to 59, 4.1 to 1,458 and -0.04 to 2,094 mg m(-2) d(-1), respectively. A significantly higher flux of N2O was found in chambers instal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 15 publications
3
41
1
Order By: Relevance
“…Values of N 2 O-N emission from our study are significantly lower than the values observed in various CWs for wastewater treatment (up to 17,000 μg N 2 O m -2 h -1 ; [13,14,16,17,72]), lower than those reported from drained boreal Grasslands [76] and wetlands with altered water regime [77] show higher N 2 O-N emission (up to 184 μg N 2 O m -2 h -1 ). Forests emit low amounts of nitrous oxide (from low consumption up to 35 μg N 2 O m -2 h -1 ; [78,79]), whereas deciduous forests tend to emit more than coniferous forests [80].…”
Section: Chcontrasting
confidence: 82%
See 2 more Smart Citations
“…Values of N 2 O-N emission from our study are significantly lower than the values observed in various CWs for wastewater treatment (up to 17,000 μg N 2 O m -2 h -1 ; [13,14,16,17,72]), lower than those reported from drained boreal Grasslands [76] and wetlands with altered water regime [77] show higher N 2 O-N emission (up to 184 μg N 2 O m -2 h -1 ). Forests emit low amounts of nitrous oxide (from low consumption up to 35 μg N 2 O m -2 h -1 ; [78,79]), whereas deciduous forests tend to emit more than coniferous forests [80].…”
Section: Chcontrasting
confidence: 82%
“…Dinitrogen (N 2 ) emission was measured using the He-O method [17,19,33,34]. Intact soil cores (diameter 6.8 cm and height 6 cm) for analysis using the H-O method were taken from the topsoil (0-10 cm) under the gas sampler (closed chamber) sites after gas sampling was completed.…”
Section: Gas Sampling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the presence of efficient electron acceptors (e.g., NO − 3 ) to prevent the reduction of N 2 O to N 2 (Bremner and Blackmer, 1981;Speir et al, 1995;Jungkunst et al, 2004). Due mainly to analytical difficulties in the determination of microbially produced N 2 , to date the denitrification potential from waterlogged peat soils has rarely been estimated (Watts and Seitzinger, 2000;Mander et al, 2003;Teiter and Mander, 2005;Wray and Bayley, 2007;Roobroeck et al, 2010;Soosaar et al, 2011;Uri et al, 2011). The substitution of ambient N 2 by Helium (He) in laboratory studies possibly represents the most reliable method for the direct and simultaneous determination of N 2 O and N 2 exchange rates (Butterbach-Bahl et al, 2002;Roobroeck et al, 2010;Butterbach-Bahl et al, 2013).…”
Section: T Eickenscheidt Et Al: Nitrogen Mineralization and Gaseousmentioning
confidence: 99%
“…For measurements of N 2 , N 2 O, CO 2 and CH 4 fluxes, we applied the helium-oxygen (He-O) method (Butterbach-Bahl et al, 2002;Mander et al, 2003;Roobroeck et al, 2010;Uri et al, 2011) using four different incubation temperatures (0, 5, 15 and 25 • C). Five replications per site and moisture content were simultaneously placed in special gas-tight incubation vessels inside a climate chamber.…”
Section: Determination Of Gas Fluxesmentioning
confidence: 99%